Could Ctesias refer to the Kalash tribe? Some thoughts on interpretation of Ctesian descriptions of India - SMYK, Anita (Historia i Świat, 2019)
Indica of Ctesias is a priceless material for research into the perception of distant lands in the Greeks, or the shaping of literary images.